Cold pools mediate mesoscale adjustments of trade-cumulus fields to changes in cloud droplet number concentration - P. Alinaghi; F. Jansson; D. A. Blázquez; F. Glassmeier (Atmospheric Chemistry and Physics)
The mesoscale self-organization of trade-cumulus cloud fields is a major cloud–climate uncertainty. Cold pools, i.e., pockets of cold, dense air resulting from rain evaporation, are a key mechanism in shaping these dynamics and are controlled by the large-scale forcing. We study the microphysical sensitivity of cloud-field self-organization through cold pools by varying the cloud droplet number concentration (Nc) from 20 to 1000 cm−3 in large-eddy simulations on large 154 km×154 km domains. We find that cold pools exhibit two distinct regimes of mesoscale self-organization. Under very low Nc conditions, cold pools transition from a stage in which they are small and randomly distributed to forming large, long-lived structures that perpetuate due to the collisions of cold pools at their fronts. Under high-Nc conditions, cold pools display strongly intermittent behavior and interact with clouds through small, short-lived structures. Thus, although Nc influences the number of cold pools and, in turn, mesoscale organization, cloud depth, and cloud albedo, we find its effect on cloud cover to be minimal. Comparing the microphysical sensitivity of cold-pool-mediated mesoscale dynamics to the external, large-scale forcing shows that Nc is as important as horizontal wind and large-scale subsidence for trade-cumulus albedo. Our results highlight that cold pools mediate the adjustments of trade-cumulus cloud fields to changes in Nc. Such mesoscale adjustments need to be considered if we are to better constrain the effective aerosol forcing and cloud feedback in the trade-wind regime.